Capacity-building interventions for health extension workers in Ethiopia: A scoping review - Tigist Astale; Helina Mesele; Sarah-Louise Pasquino; Anteneh Zewdie; Eskinder Wolka; Aklilu Endalamaw; Yibeltal Assefa; Getnet Mitike (PLoS ONE, 2025)
Introduction Capacity-building interventions for health extension workers (HEWs) are key to providing quality health services to the community. Since Ethiopia’s Health Extension Program was established, several types of capacity-building interventions have been developed to build HEW competencies. However, no comprehensive study has mapped the types of capacity-building interventions being used or the competencies targeted. Objective To (1) identify and characterize evidence on capacity-building interventions for Ethiopian HEWs, including the competencies measured; (2) clarify evidence gaps in this area; and (3) explore how successful the interventions have been to inform the design of health extension programs and further research. Methods We used keywords (health extension workers, capacity building, competencies) and related terminologies to search PubMed, Scopus, and Embase for published studies on capacity-building interventions for Ethiopian HEWs, and Google Scholar for unpublished studies and reports. Our search was limited to studies and reports published in English from 2003 to present. We used the JBI scoping review methodology to conduct this scoping review in a stepwise approach and a categorization approach to synthesize the evidence. Results Our search strategy identified 20 articles, all published except for one program report. The most common capacity-building intervention designed for HEWs was training, followed by supportive supervision, performance review and clinical mentoring meetings, and equipment supply; the most salient competency domains investigated were knowledge and skills. The interventions significantly improved immediate outcomes (knowledge, skills, attitude change among HEWs) and intermediate outcomes, such as increased service utilization and health-seeking behavior among community members. Only one study assessed whether capacity-building interventions improved inter- and intra-personal domains of capacity/competency. Conclusions Capacity-building interventions for Ethiopian HEWs were found to be effective, but they mainly focused on improving technical competencies, such as knowledge and skills. Little attention has been paid to other competency domains, including motivation, leadership, and communication. Thus, future research could focus on a comprehensive set of capacity-building initiatives that addresses motivation, job satisfaction, communication, commitment, and resource allocation.